UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAMES TOURNAMENT (TGT) PADA MATA PELAJARAN PPKN KELAS XI MA NURUL FALAH TELUK PAKEDAI KABUPATEN KUBU RAYA - Sayeni Anjelika; Bambang Budi Utomo; Thommy Sastra Atmaja (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The purpose of research at the MA Nurul Falah school is to improve learning outcomes that are a problem for teachers and students by using the team games tournament learning model. The research was conducted at the school of MA Nurul Falah Teluk Pakedai, Kubu Raya Regency in class XI with 38 students. Researchers used descriptive methods, more precisely classroom action research. The techniques used are direct observation techniques, direct communication techniques, measurement techniques and finally documentary techniques and instruments used are observation, interview guides, learning outcomes and documentaries. This study used 2 cycles, in the first cycle the average score was 70.26 and 21 students succeeded in achieving the KKM completeness only 55.26% and 17 participants did not reach the KKM completion as much as 44.74%. And in the second cycle there was an increase of 13.42 now to 83.68 and categorized as high, 30 students succeeded in reaching the KKM with a completeness percentage of 78.95% and only 8 participants did not reach the KKM incomplete only 21.05%, Data analysis shows that there is a change in results learning got better and improved after using cooperative learning team games tournament in class XI MA Nurul Falah Teluk Pakedai. Keywords: Efforts, PPKn, Team Games Tournament